PERANCANGAN BATCH MIXER UNTUK PENGADUKAN BASE SOAP BERBASIS INTERNET OF THINGS (IoT) DI IKM TA REZEKI, KOTA MEDAN - Tengku Rachmi Hidayani; Sry Wahyuni; Poltak Evencus Hutajulu; New Vita M.D Marbun; Meutia Mirnandaulia; Krissandarta Tarigan; Benny Rio Fernandez; Fransnazoan Sitorus (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Small and Medium Industries (SMEs) play an important role in the regional and national economy, especially in providing employment and increasing the added value of local products. T.A Rezeki is one of the SMEs that produces its products by purchasing raw materials from products at chemical stores, then marketing them to surrounding areas, several restaurants, mosques and laundries directly. The design of an IoT-based batch mixer is expected to help TA Rezeki SMEs to automate the base soap stirring process so that it is more efficient and consistent. With the implementation of IoT, it is expected to reduce operational costs, increase production capacity, and produce soap products with better and uniform quality. Based on the satisfaction survey conducted, the results showed that the digitalization of soap stirring tools carried out in this activity provided benefits to SMEs by providing convenience with equipment automation and more consistent stirring so that the resulting products are also of better quality.